Pausing to Consider the Impact of Cultural Trends On Mental Health Treatment - Peter J. , O’Brien (International Journal of Psychosocial Rehabilitation, 2013)
The article raises concerns about a focus on efficiency and cost-containment as the main factors in evaluating psychotherapeutic practice. Pausing to consider the impact of cultural trends on therapy can lead to an accent on therapist discretion is an integral ingredient of the therapeutic process that can promote good outcomes for the client and personal satisfaction for the therapist.